Evaluating the Potential of Chromium Resistant Bacteria Isolated from Industrial Effluents for Indole Acetic Acid (IAA) Production: Isolation of Indole Acetic Acid f rom Chromium Resistant (Biological Sciences - PJSIR, 2025)
In Pakistan, more than 800 tannery industries are present. Untreated industrial effluents lead  to contamination of nearby soil, aquatic life, groundwater quality and ultimately humans by noxious heavy metals and other contaminants. The current study has designed to evaluate potential of indole acetic acid (IAA) synthesis from chromium resistant bacteria extracted from industrial effluents. A total of 20 samples of wastewater and adjacent soil were collected from 5 different tannery industries of Gujranwala and Lahore, Pakistan. Sequestration of bacteria resistant to chromium was done by spread plate method and further proceeded by screening test for IAA production. Bacteria resistant to chromium were cultured in LB media and centrifugation was done at gravitational acceleration of 18,894 g for 20 min to obtain  supernatant. Salkowski reagent added to supernatant in (2:1) ratio. Five Cr resistant bacteria which confirmed maximum IAA production were further examined by applying different experimental conditions such as variation in pH, temperature, Trp (tryptophan) concentration and inoculum size. Investigations revealed that, isolated chromium resistant bacteria showed maximum IAA production at 37 °C and acidic pH. The isolated Cr resistant bacteria showed increase in IAA production by increasing Trp (tryptophan) concentration and inoculum size. Sequestration of bacteria resistant to chromium from industrial waste will be beneficial for IAA production which can be further applied for plant growth enhancement as bio-fertilizer.